Studies on Variability, Heritability, Genetic Advance and Divergence for Earliness, Yield and Yield Components in Rice (Oryza sativa L.) Genotypes - Sreedhar, S. (International Journal of Bio-resource and Stress Management, 2018)
Thirty one genotypes derived through pedigree method of breeding were studied for estimation of genetic variability and divergence at Agricultural Research Station, Kunaram. The GCV and PCV were high for number of grains panicle-1 and 1000-grain weight, whereas, low for panicle length and plant height. Additive gene action was predominant for 1000-grain weight, number of grains panicle-1, days to 50 % flowering and grain yield as they registered high heritability coupled with high genetic advance values. Based on D2 analysis, 31 genotypes were distributed into five clusters with the cluster II containing maximum number of genotypes followed by cluster I. Highest inter cluster distances were observed between the clusters III and V followed by I and IV, and IV and V suggesting wide diversity between the traits. Cluster mean analysis revealed that genotypes from the clusters IV and III would be used in breeding programme to develop varieties of medium slender fine grain varieties as they recorded more number of grains panicle-1 and low 1000-grain weight and also these genotypes were characterized by early and medium duration flowering duration. The genotype, RDR 1156 was identified as a potential genotype for developing early duration, long bold or long slender grain varieties. Among the traits studied, days to 50% flowering and 1000-grain weight manifested highest contribution towards total divergence, thus, these traits could be given due importance for further crop improvement in the present material.